(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
By the title Depictionof Nature in the Sculptural Art of Early Deccan, we mean to understandhow nature, Le., fauna and flora in the context of the present study, came to beconceptualized by the sculptor in its depiction on sculptural art thatprimarily reflected his perception of understanding nature as he saw it. Italso involved representation that was usually embedded in a religious meaningor symbolism that was being conveyed since many of the monuments on which thissculptural art was (bund were centers of worship. Hitherto, very few scholarshave exclusively studied nature in sculpturalari but a large majority ofthese studies have focused on understanding it only as a marginal or decorativepart of art history. In fact, no special attention has been made to study thedepiction of nature in its varied natural forms in the context of regionalhistory. Therefore, the present research undertaken by us in this thesis essentiallyaims at describing the depiction of nature in sculptural art in a regionalcontext, namely, of the early Deccan. In an overall sense this wasconceptualized by the sculptor to be embedded in a naturalism that wasessentially linked to an ideological belief system that saw human interventionwith nature in a holistic and integrative way rather than being separated fromit.